Cancer Stem Cell Subpopulations Are Present Within Metastatic Head and Neck Cutaneous Squamous Cell Carcinoma - Kilmister, Ethan J.; Patel, Josie; van Schaijik, Bede; Bockett, Nicholas; Brasch, Helen D.; Paterson, Erin; Sim, Dalice; Davis, Paul F.; Roth, Imogen M.; Itinteang, Tinte; Tan, Swee T. (Frontiers in Oncology, 2020)
Cancer stem cells (CSCs) have been identified in many cancer types including primary head and neck cutaneous squamous cell carcinoma (HNcSCC). This study aimed to identify and characterize CSCs in metastatic HNcSCC (mHNcSCC). Immunohistochemical staining performed on mHNcSCC samples from 15 patients demonstrated expression of induced pluripotent stem cell (iPSC) markers OCT4, SOX2, NANOG, KLF4 and c-MYC in all 15 samples. In-situ hybridization and RT-qPCR performed on four of these mHNcSCC tissue samples confirmed transcript expression of all five iPSC markers. Immunofluorescence staining performed on three of these mHNcSCC samples demonstrated expression of c-MYC on cells within the tumor nests (TNs) and the peri-tumoral stroma (PTS) that also expressed KLF4. OCT4 was expressed on the SOX2+/NANOG+/KLF4+ cells within the TNs, and the SOX2+/NANOG+/KLF4+ cells within the PTS. RT-qPCR demonstrated transcript expression of all five iPSC markers in all three mHNcSCC-derived primary cell lines, except for SOX2 in one cell line. Western blotting showed the presence of SOX2, KLF4 and c-MYC but not OCT4 and NANOG in the three mHNcSCC-derived primary cell lines. All these three cell lines formed tumorspheres, at the first passage. We demonstrated an OCT4+/NANOG+/SOX2+/KLF4+/c-MYC+ CSC subpopulation and an OCT4+/NANOG-/SOX2+/KLF4+/c-MYC+ subpopulation within the TNs, and an OCT4+/NANOG+/SOX2+/KLF4+/c-MYC+ subpopulation within the PTS of mHNcSCC.